Assessing microbial manipulation and environmental pollutants in the pathogenesis of psoriasis - Gough, Portia; Zeldin, Jordan; Myles, Ian A. (Frontiers in Immunology, 2022)
The cutaneous microbiome is increasingly recognized as a contributor to skin diseases like atopic dermatitis (AD) and psoriasis. Although traditionally AD and psoriasis have been viewed as having opposing immunologic findings, resent evidence suggests an overlap in ceramide-family lipid production in the protection against symptoms. We recently identified that specific environmental pollutants may drive dysbiosis through direct suppression of ceramide-family lipids produced by health-associated skin bacteria in atopic dermatitis (AD). We further demonstrated that one such bacteria, Roseomonas mucosa, generated significant clinical improvement in AD lasting beyond active treatment via lipid-mediated modulation of tumor necrosis factor (TNF) signaling. To assess the potential preclinical benefit of R. mucosa in psoriasis we assessed for direct effects on surface TNF signaling in cell cultures and identified direct effects on the TNF axis. We also identified preclinical efficacy of R. mucosa treatment in the imiquimod mouse model of psoriasis. Finally, we expanded our previous environmental assessment for psoriasis to include more traditional markers of air quality and found a strong association between disease rates and ambient carbon monoxide (CO), nitrogen dioxide (NO2), and particulate matter (PM). At the current stage this work is speculative but does support consideration of further preclinical models and/or clinical assessments to evaluate any potential for therapeutic benefit through microbial manipulation and/or environmental mitigation.